History of the Decline and Fall of the Roman Empire Complete and Unabridged - Edward Gibbon (Abraham Small and M. Carey, 1776)
Notice issue d Open Library. Titre: History of the Decline and Fall of the Roman Empire Complete and Unabridged. Auteur: Edward Gibbon. Ouvrage retenu pour enrichir la partie histoire et Géographie.
Métadonnées bibliographiques issues d Open Library
Keywords: open library; histoire; Géographie; livre; C.; 20 av. J.; Open Library Staff Picks; Histoire